Efeitos sinérgicos de adições minerais em concretos por empacotamento de partículas: resistência à compressão axial, microestrutura e absorção de água - Feltrin, Cristina Silva (2019)
This research aims to study the physical, chemical and synergistic effects of lime filler (LF), fly ash (FA) and rice husk ash (RHA) addition in concretes dosed from particle packing theories. Both mixtures alone (binary mixtures) and joint mixtures (ternary mixtures) were investigated in order to verify their influence on the internal structure of the concrete at the micro and meso level. Some variables that influence the microstructure and durability of the concrete are highlighted, such as compressive strength, calcium hydroxide (CH) content, chemically combined water content (H), chemical compounds formation and water absorption. The results were analyzed in an integrated (holistic) way. The integrated study of the connection between the use of mineral additions and particle packing, especially in ternary mixers of pozzolans and among pozzolans, unites the nano/microstructure with the meso/macrostructure of aggregates, thus enabling the investigation of the transformations of the phases of concrete in a single study, between the dimensions of the particles and pores and the respective compounds formed from their atomic-molecular structure. From the analysis and interpretation of the results, we concluded that when two mineral additions are added together to Portland cement in a ternary system, a synergistic effect between them occurs, which results in better performance of these mixtures in relation to strength and durability compared to mixtures with only one addition of a less reactive mineral. The synergistic effect between the carbonate material and pozzolans occurs mainly for low ag/ agl ratios and between FA and RHA pozzolans occurs for both low and high ag/agl ratios. This synergistic effect results from the overlapping physical and chemical positive effects of one or the other addition causing a higher final sum effect than that of the single addition. This result is verified mainly due to the higher hydrated compound content (chemically combined water content) caused by the higher consumption of CH due to the pozzolanic reaction or the greater physical effect of particle packing and nucleation, depending on the ag/agl ratio.